2013
DOI: 10.1017/s1751731113000566
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-stimulating diets during the weaning-to-estrus interval do not improve fetal and placental development and uniformity in high-prolific multiparous sows

Abstract: Piglet birth weight and litter uniformity are important for piglet survival. Insulin-stimulating sow diets before mating may improve subsequent piglet birth weights and litter uniformity, but the physiological mechanisms involved are not clear. This study evaluated effects of different levels of insulin-stimulating feed components (dextrose plus starch; fed twice daily) during the weaningto-estrus interval (WEI) on plasma insulin and IGF-1 concentrations, and on follicle development and subsequent luteal, feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
6
13
0
2
Order By: Relevance
“…The associations of insulin and IGF-1 responses between treatments are confirmed by associations found between insulin and IGF-1 in other studies (van den Brand et al, 2001;Wientjes et al, 2013;and reviewed by Thissen et al (2004)). However, the same studies report that dietary treatments did not significantly affect IGF-1 levels.…”
Section: Insulin Like Growth Factorsupporting
confidence: 69%
See 3 more Smart Citations
“…The associations of insulin and IGF-1 responses between treatments are confirmed by associations found between insulin and IGF-1 in other studies (van den Brand et al, 2001;Wientjes et al, 2013;and reviewed by Thissen et al (2004)). However, the same studies report that dietary treatments did not significantly affect IGF-1 levels.…”
Section: Insulin Like Growth Factorsupporting
confidence: 69%
“…These higher insulin and glucose levels in the carbohydrate treatment coincide with higher IGF-1 levels in gilts receiving the C À treatment. Previous experiments from literature with insulin stimulating diets (high carbohydrates) report similar results for glucose and insulin on the short term (van den Brand et al, 1998(van den Brand et al, , 2000Wientjes et al, 2012Wientjes et al, , 2013. In comparison to the C þ treatment, the C À treatment had less glucogenic compounds in the feed and the increase in glucose on the longer term for gilts in the C À treatment may reflect glycogenolysis to increase glucose levels for the citric acid cycle (van Knegsel et al, 2005).…”
Section: Glucose and Insulinsupporting
confidence: 56%
See 2 more Smart Citations
“…Our results also showed insulin effects on the ovary, improving follicle growth and subsequent ovulation rate. In contrast, the recent study of Wientjes et al (2013) reported that insulin-stimulating diets fed to hyperprolific multiparous sows during the weaning-to-estus interval did not improve follicle development and uniformity of fetuses and placentas, which emphasizes the metabolic differences between the cyclic gilt and the lactating and weaned sows experimental models.…”
Section: Discussionmentioning
confidence: 73%